Making exit costly but efficient: The political economy of exit clauses and secession - Martijn Huysmans; Christophe Crombez (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
This article presents a political economic analysis of exit from federations. Over time, members' benefits from being in a federation can fluctuate because of changes in the state of the world. If a member stops benefitting, it may wish to secede i.e. exit the federation. Based on a real options model, we show that state-contingent exit penalties can induce socially efficient exit decisions. In addition to the substantive implications, this represents a methodological contribution to real options theory. Even if ex-ante specified exit penalties cannot be made state-contingent, they may still enhance social welfare by preventing secession wars. This finding runs counter to the dominant view in the literature that exit clauses should be avoided in federations. As a first test of the model, we derive five hypotheses and show that they hold for the breakup of Yugoslavia and all cases known to us of federations with an exit clause.
Keywords: 330; Exit Clauses; Secession; Federalism; Real Options